The New ID Proof: A Case Report of Denture Labeling - Gujjalapudi, Mahalakshmi; Anam, Chandrasekar; Mamidi, Praveen; Saxena, Aarti; Kumar, Gautam; Rathinam, Jothi (Journal of Orofacial Research, 2013)
Denture labeling is not a new concept in either prosthetic or forensic dentistry and its routine practice has been urged by forensic dentists internationally for many years. Prosthodontistsare playing very important role in forensic dentistry as they are concerned with fabrication of various prostheses which can serve as an important tool for identification. The main objective of this article is to discuss the various methods available for denture marking along with a case report.